2019
DOI: 10.1016/j.immuni.2019.05.011
|View full text |Cite
|
Sign up to set email alerts
|

IL-10-Dependent Crosstalk between Murine Marginal Zone B Cells, Macrophages, and CD8α+ Dendritic Cells Promotes Listeria monocytogenes Infection

Abstract: Highlights d Loss of marginal zone (MZ) B cells reduces intracellular Listeria in CD8a + cDC1s d Listeria stimulates MZ B cells to produce IL-10 via a MyD88dependent pathway d IL-10 does not directly alter cDC1 handling of bacteria or antigen presentation d IL-10 inhibits iNOS and increases splenic macrophage intracellular bacterial burden

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 74 publications
0
24
0
Order By: Relevance
“…Although more studies will need to be performed to examine this, these potential alternate methods of transit could impact antigen uptake and subsequently, presentation to naïve T cells. Finally, while previous studies have demonstrated a profound Batf3 cell-extrinsic effect on the induction of Lm-specific CD8 T cell responses (16,17), mice used in this study also lack Batf3 expression in CD8 T cells that may influence the T cell responses at higher infectious doses.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Although more studies will need to be performed to examine this, these potential alternate methods of transit could impact antigen uptake and subsequently, presentation to naïve T cells. Finally, while previous studies have demonstrated a profound Batf3 cell-extrinsic effect on the induction of Lm-specific CD8 T cell responses (16,17), mice used in this study also lack Batf3 expression in CD8 T cells that may influence the T cell responses at higher infectious doses.…”
Section: Discussionmentioning
confidence: 66%
“…This is in contrast to the restoration of pathogen burden during i.v. Lm infection, where Lm-specific CD8 T cell responses were rescued in Batf3 −/− mice (16,17). Altogether, these data suggest that cDC1 may play an important role in driving effector CD8 T cell responses after foodborne InlA M Lm infection.…”
Section: Infection (Supplementarymentioning
confidence: 72%
See 2 more Smart Citations
“…This regional segregation of cDC1 raises the question of the division of labor within the cDC1 population in the spleen: the red pulp cDC1 subset may be more prone to interact with innate cells, whereas the T cell zone cDC1 subset may be poised to initiate adaptive responses. Interestingly, systemic administration of poly(I:C), red blood cells, or Listeria triggers red pulp cDC1 repositioning in the marginal zone of the white pulp, and in the T cell zone where antigenbearing mature cDC1 have more chance to interact with naïve T cells (Alexandre et al, 2016;Liu et al, 2019;Idoyaga et al, 2009;Calabro et al, 2016). CCR7 is suggested to be a master regulator of the migration of red pulp cDC1 into the T cell zone (Calabro et al, 2016).…”
Section: Introductionmentioning
confidence: 99%